Studies On Pollution Of Ashtamudi Estuary And Ground Water Due To Dumping Of Municipal Solid Wastes At Kureepuzha, Kollam, And Its Environmental Impacts - Najee M and M C Philipose (The journal of the Institution of Public Health Engineers, 2013)
This study is focused on the variation of physico-chemical parameters in water samples taken from two different sites of the lake and from 6 wells near the dumpsite. The Dissolved Oxygen(DO) content and Total Dissolved Solids(TDS) content of most of the samples are beyond the standard limits. The chloride content near the dumpsite is found to be very high when compared to the non-polluted site of the lake.